Optical properties of porcine dermis in the mid-infrared absorption band of glucose - Schönhals, Arthur; Kröger-Lui, Niels; Pucci, Annemarie; Petrich, Wolfgang (The analyst, 2017)
The optical properties of skin in the mid-infrared range are not known, despite their importance for e.g. non-invasive glucose monitoring. In this paper, transmission, absorption, scattering, and reduced scattering coefficients are quantified using a custom-built goniometer based on a quantum cascade laser operated at the glucose absorption band at a wavelength of around 9.7 μm. The measurements show a strong dominance of absorption and moderate contributions from scattering. The scattered radiation is dominated by single scattering events in the forward direction (g = 0.967) within the range of the investigated dermis layer thicknesses of up to 50 μm, whereby the fraction of multiple scattering is expected to increase with the layer thickness.